Evaluation of the Implementation of Cross Interest Physics Subject for Non-Mathematics and Natural Sciences Students at Senior High School - Vivin Khoiri Yanti; Suliyanah Suliyanah; Nur Shabrina Safitri; Utama Alan Deta (Journal of Innovation in Educational and Cultural Research, 2021)
Cross-interest is a program that aims to expand and develop students' interests, talents and abilities by selecting subjects outside the specialization program group. The cross-interest program has been implemented for several years in Indonesia, but there is still very little evaluation of the implementation of this program, especially across physics interests. For the implementation of cross-interest physics to be more optimal, research related to cross-interest program evaluation in physics is needed. This study aims to evaluate cross-interest programs in physics and identify obstacles in its implementation hence the solutions can be formulated. This study involved 203 social science students as respondents from schools which implementing cross-interest physics programs. This type of research uses evaluative research with qualitative descriptive methods, where data collection is compiled using questionnaires and interviews which are conducted online. The results of this study indicate that there are still several obstacles in the implementation of cross-interest classes in physics, including the inadequacy of class grouping across interests with student interests, lack of teacher teaching hours, and lack of participation and enthusiasm of cross-interest class students compared to specialization class students. Based on the research results, it can be concluded that the implementation of the cross-interest program in physics is still below expectation. Through the results of this research, it is presented an evaluation material and become a consideration for the relevant parties in charge of implementing the cross-interest physics program subsequently there will be improvements in the implementation of cross-interest physics program purposefully.